2001
DOI: 10.1093/ndt/16.6.1262
|View full text |Cite
|
Sign up to set email alerts
|

An experimental sclerosing encapsulating peritonitis model in mice

Abstract: We have developed a convenient experimental model of SEP in mice, which may be useful in elucidating the pathogenesis of SEP and in establishing possible treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 11 publications
1
74
1
1
Order By: Relevance
“…[16,17] Junor and colleagues first described the role of gluconate and alcohol in the pathogenesis of peritoneal fibrosis in 1985. [10] They reported the development of Effects of Low-Dose ESA on Peritoneal Fibrosis 571 clinical ESP when peritoneal catheter gets sterilized by chlorhexidine gluconate in alcohol. Upon this finding, Ishii and colleagues showed the development of peritoneal fibrosis in test animals by using 0.1% chlorhexidine gluconate and 15% alcohol dissolved in saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] Junor and colleagues first described the role of gluconate and alcohol in the pathogenesis of peritoneal fibrosis in 1985. [10] They reported the development of Effects of Low-Dose ESA on Peritoneal Fibrosis 571 clinical ESP when peritoneal catheter gets sterilized by chlorhexidine gluconate in alcohol. Upon this finding, Ishii and colleagues showed the development of peritoneal fibrosis in test animals by using 0.1% chlorhexidine gluconate and 15% alcohol dissolved in saline.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the study was 12 days. To induce peritoneal fibrosis, we used a model described by Ishii and et al [10] that composed of 0.1% CH and 15% ethyl alcohol dissolved in saline prepared in aseptic era. Epoetin beta (Neorecormon, F. Hoffmann-La Roche Ltd., Basel, Switzerland) was used as 1000 IU/0.3 ml.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 The latter two agents caused peritoneal adhesions that were very similar to those seen in patients with encapsulating peritoneal sclerosis (EPS), a serious complication of long-term PD therapy. Although the mechanism underlying the development of peritoneal fibrosis by CG is unclear, previous reports have shown that persistent chemical irritation by CG could induce tissue damage with inflammation characterized by infiltration of macrophages followed by excessive proliferation of fibroblasts.…”
Section: Introductionmentioning
confidence: 93%
“…The animals were followed for 56 days. All animals in the group that used chlorhexidine and alcohol 18 developed encapsulating peritonitis 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Ishii et al 5 developed a model in mice using intraperitoneal injection of chlorhexidine gluconate 0.1% and 15% ethanol dissolved in saline at a dose of 0.3 ml daily, using buffered saline in the control group. The animals were followed for 56 days.…”
Section: Introductionmentioning
confidence: 99%